Targeted muscle reinnervation at the time of amputation to prevent the development of neuropathic pain - Raasveld, Floris V.; Mayrhofer-Schmid, Maximilian; Johnston, Benjamin R.; Gomez-Eslava, Barbara; Hoftiezer, Yannick A. J.; Liu, Wen-Chih; Valerio, Ian L.; Eberlin, Kyle R. (Journal of plastic, reconstructive & aesthetic surgery, 2024)
Introduction - Targeted muscle reinnervation (TMR) is an established modality for the surgical management of neuropathic pain. Although the preventive effect of primary (acute) TMR at the time of amputation has been demonstrated previously, it remains unclear how many and which patients benefit most. Therefore, this study investigated the proportion of patients achieving sustained pain prophylaxis following amputation, as well as factors associated with its efficacy. - Methods - Primary patients who underwent TMR with a minimum follow-up of 6 months between 2018 and 2023 were enrolled. Pain outcomes (numeric rating scale [NRS], 0-10), comorbidities, and surgical factors were collected from chart review. Patients achieving sustained pain prophylaxis (NRS of ≤3 for ≥3 months until final follow-up) were identified. Multilevel mixed-effect models and multivariable regression were used to visualize pain courses and identify associated factors. - Results - Seventy-five patients who underwent primary TMR were included (median follow-up: 2.0 years), of whom 57.3% achieved sustained pain prophylaxis whereas 26.7% reported pain disappearance. Distal amputation levels (p = 0.036), a lower Elixhauser Comorbidity Index (p = 0.001), and the absence of psychiatric comorbidities (p = 0.039) were associated with pain prophylaxis. - Conclusion - This study demonstrates that more than half of all patients undergoing primary TMR achieved sustained pain prophylaxis, and approximately a quarter of patients achieved sustained pain disappearance. Several factors associated with these favorable outcomes are described. These results will aid in preoperative counseling, managing patient expectations, and selecting patients who may benefit most from primary TMR surgery. - Level of Evidence - IV - Therapeutic